Gerakan Literasi Budaya: Pemanfaatan Cerita Huma Betang sebagai Media Pembelajaran Menulis Teks Naratif di SMP - rahman, rahman; Diplan, Diplan; Helmi, Helmi; Hariatam H, Fendy (Jurusan Pendidikan Ilmu Pengetahuan Sosial, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2025)
This community service program aims to improve junior high school students' narrative writing skills through the use of Huma Betang stories as a local wisdom-based learning medium. The noble values of Huma Betang, such as togetherness, tolerance, and mutual cooperation, are integrated into the learning material so that students not only acquire literacy skills but also a deeper understanding of culture. This activity was carried out through a series of creative writing training sessions, classroom mentoring, and the provision of learning modules based on the Huma Betang story. The methods used included interactive lectures, discussions, story exploration, and gradual narrative writing practice. The results of the activity showed that students were more enthusiastic in participating in the learning process, were able to develop story ideas in a more structured manner, and demonstrated improved skills in language, plot, and creativity. In addition, teachers gained an alternative innovative and contextual learning model. This program is expected to become a model for strengthening literacy based on local culture that can be replicated in other schools, as well as an effort to preserve the values of Huma Betang among the younger generation. Thus, this community service provides a real contribution to improving the quality of Indonesian language learning through a relevant and meaningful cultural approach.